NATIONAL IDEA: THE CULTURAL ASPECT - Бабій, Л. Т. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article analyses the cultural aspect of the Ukrainian national idea in the context of modern globalizational processes. It highlights the connection of national idea and Ukrainian mentality which is considered from social-cultural but not genetic viewpoint.